Public oversight over audit as a determinant of its quality - Đorđević, Milica; Đukić, Tadija (BizInfo Blace, 2022)
Ensuring a high level of audit quality is a basic prerequisite for fulfilling its purpose - increasing the credibility of information contained in financial reports and functioning in the public interest. Since the self-regulation of the audit profession has not proven to be a sufficient mechanism for ensuring the quality of audits in the last two decades the need and importance of establishing and effectively functioning public oversight over audits is especially highlighted. The aim of the authors of this paper is to assess the compliance of the institutionalization of public audit oversight in the Republic of Serbia with the relevant European Union regulations and the manner of its functioning. In order to examine the direction of further development of public oversight and, in particular, its impact on audit quality, an analysis of the practice of public oversight in the Republic of Serbia for the last four years was carried out.
Keywords: audit quality; chamber of authorized auditors; the securities commission; the audit public oversight board; eighth directive